EFEKTIVITAS BUAH PISANG TERHADAP PENURUNAN TEKANAN DARAH DIASTOL PADA IBU HAMIL DI PUSKESMAS BARUGA KECAMATAN PAJUKUKANG KABUPATEN BANTAENG - Rosdianah Rosdianah; Irmawati Sadullah (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2023)
Hypertension in pregnancy is 5-15% of pregnancy complications and is one of the three highest causes of maternal mortality and morbidity. Bananas have a high potassium content which can help reduce and lower blood pressure. pre-experimental method, in this study using non-probability sampling using the one group pre-test post-test design. The sample in this study were 15 people with a purposive sampling technique. Data were collected using observation sheets and analyzed using a paired T statistical test (Payred Sample Test) with a short significance p(α) = 0.05. The results of the analysis showed that bananas were effective in reducing blood pressure in pregnant women with a value of p = 0.000. Because the value of p = 0.000 <0.05 this means that Ho is rejected and Ha is accepted. Thus there is an effect of giving bananas on reducing diastolic blood pressure in pregnant women. It can be concluded that giving bananas is effective in reducing diastolic blood pressure in pregnant women and can be used as an alternative to overcome the occurrence of hypertension in pregnancy